CAN THE INTERNAL CONTROL SYSTEM REDUCE FRAUDULENT USE OF VILLAGE FUNDS IN ADVERSE SELECTION CONDITION? - Sitanala, Theresia Febiengry (Jurnal Tata Kelola & Akuntabilitas Keuangan Negara, 2019)
In recent years, corruption cases at the village level have been in the public spotlight. This was evidenced through around 154 corruption cases at the village level involving 112 village heads, 32 village officials and 3 village heads. This corruption case resulted in the state experiencing a loss of 47.56 billion rupiah during 2015-2017. This case is carried out through various modes such as the practice of budget abuse, fictitious reports, fictitious activities/projects, and budget bubbles. These various modes occur because the internal control system is ineffective, so it provides an opportunity for actors to act opportunistically. The goal is to maximize his personal interests as agents rather than the interests of the community as principals. This opportunistic behavior is caused by the existence of information asymmetry. Information asymmetry creates conditions for obtaining information that is not aligned between the village head as an agent and the community as the principal, so that the emergence of adverse selection. This study aims to examine the effect of the internal control system on fraudulent use of village funds in agency conflict conditions through adverse selection. This study used the laboratory experiment method with the subject being Accounting Student at Pattimura University Ambon. The data analysis technique uses Two-Way ANOVA with a 2x2 factorial experimental design. The results of the study show that (1) adverse selection conditions affect the relationship between the internal control system and fraudulent use of village funds, (2) the internal control system that does not effectively affect fraudulent use of village funds under adverse selection is compared to no adverse selection (3 ) adverse selection conditions do not affect fraudulent use of village funds when the internal control system is effective, and (4) in the absence of adverse selection, an effective internal control system will reduce fraudulent use of village funds compared to ineffective internal control systems.